Development of shear horizontal surface acoustic wave with silicon dioxide nanoparticles waveguide sendor for escherichia coli O157: H7 detection - Ten, Seng Teik (Institute of Nano Electronic Engineering, 2017)
There were four main scopes in this research works. All the research scopes were arranged in the flow order; one had to be completed before the next one started. The first scopes involved simulation using COMSOL Multiphysics software with Dell Workstation which was the most computational power in the university, Precision T7600 with 2.0 GHz eight core processor with 64GB, 1600 MHz DDR3 ECC RDIMM memory. The simulation was undertaken to determine whether IDT parameters (number of finger pairs, aperture and delay length) were able to affect the SHSAW mass loading sensitivity.